Depression severity levels and cognitive functions in institutionalized elderly patients - Stella, Florindo [UNESP]; Brum, Cinthia Vieira [UNESP]; Govone, José Sílvio [UNESP] (My University, 2006)
Depression is a highly prevalent illness among institutionalized aged and assumes peculiar characteristics such as the risk for progressing to dementia. The aims of this study was to assess the cognitive functions of institutionalized elderly with clinical diagnosis of depression and compare the severity of depressive symptoms with cognitive performance. From 120 residents at a nursing home in Rio Claro, Brazil, we study 23 individuals (mean age: 74.3 years; mean schooling: 4.0 years) with diagnosis of depression. At first, a clinical diagnosis of depression and measurement of its symptoms using the Geriatric Depression Scale were performed. The patient then underwent a neuropsychological assessment based on the following tests: Mini-Mental Examination, Verbal Fluency, Visual Perception, Immediate Memory, Recent Memory, Recognition, Clock Drawing Test. The patients were divided into two groups: those with less severe depression symptoms (Group 1: N=9) and more severe symptoms (Group 2: N=14). The significant difference between symptom severity of the two groups was p=0.0001. Patients with more severe symptoms revealed a slightly inferior cognitive performance in most of the tests when compared to those with less severe symptoms (p>0.05). In relation to Verbal Fluency, patients with more severe depression symptoms presented a significantly inferior cognitive performance when compared to those with less severe symptoms (p=0.0082). Verbal Fluency revealed to be a more sensitive test for measuring early cognitive alterations in institutionalized aged with depression, and appears to be a useful resource in monitoring the cognitive functions of patients faced with the risk of dementia. © Copyright Moreira Jr. Editora.
Keywords: Aged; Cognitive functions; Depression; Neuropsychology; adult; aged; cognition; controlled study; dementia; depression; disease severity; elderly care; female; human; major clinical study; male; mini mental state examination; neuropsychological test; recognition; residential home; short term memory; symptomatology; verbal communication; vision